Automated Microsampling Technologies and Enhancements in the 3Rs - David Hopper, L. (ILAR journal, 2016)
Data collected in vivo is essential for advising decisions on drug screening and development and basic research, and animal models are used extensively for acquiring experimental measurements. Traditionally, collection of specimens has been invasive, stressful to animal subjects, labor intensive, time-consuming and costly, and required many animals when using small models with low fluid volumes, such as rats or mice. Utilizing automated microsampling (AMS) alone or in an integrative pharmacology approach to evaluate multiple physiological, pharmacokinetic, and pharmacodynamic endpoints simultaneously in the same animal accomplishes multiple experimental goals. Use of AMS robotics and associated instrumentation can assist in achieving significant reduction and refinement of animal use. Automated robotic instrumentation for specimen collection from living animal models can now be used to provide better quality pharmacokinetic and pharmacodynamic data, reduce time, provide more data with less variability, reduce animal use, and refine animal model use to reduce pain and stress. Instrumentation in common use for automated sampling and dosing is briefly discussed. In parallel with advances in automated instrumentation, recent advances in analytical detection methods complement the use of automated technology for data and specimen collection. Methods requiring much smaller volumes can now be utilized. Microsampling (small biological samples in volumes of 5-100 μL) can facilitate reduction in animal numbers while minimizing stresses associated with excessive fluid volume removal. Innovations in automation, microsampling techniques, and analytical methods have facilitated advances in data collection that allow for more robust and accurate data, reduction in animal use, and refinement in techniques that improve animal welfare. These innovations offer opportunities for wider application in nonclinical investigations by collection of multiple data streams simultaneously from individual animals. Many benefits are achievable through the use integrative pharmacology designs utilizing AMS, including decreased time for completion of composite data collection, decreased personnel resources, lower costs, improved safety, higher quality and multiple data-sets, and improvements in aspects of the 3Rs.